Mindfulness-Based Stress Release Program for University Employees: A Pilot, Waitlist-Controlled Trial and Implementation Replication. Issue 10 (October 2016) - Koncz, Rebecca; Wolfenden, Fiona; Hassed, Craig; Chambers, Richard; Cohen, Julia; Glozier, Nicholas
Abstract : Objective: The aim of this study was to evaluate the effectiveness of a 6-week mindfulness-based stress release program (SRP) on stress and work engagement in fulltime university employees. Methods: Perceived stress, workplace wellbeing, and engagement were measured at baseline and within 1 week of the SRP completion, and contemporaneously 6 weeks apart for a waitlist control group. A second program was implemented to examine reproducibility of results. Results: Fifty participants undertook the SRPs, and 29 participants were waitlisted. A significant improvement in distress, workplace wellbeing, and vigor was observed within the first SRP group, when compared with the control group. The improvement in distress and wellbeing was reproduced in the second SRP group. Conclusions: This study adds to the growing body of research that mindfulness may be an effective method for reducing workplace stress, improving employee wellbeing, and enhancing work engagement. Abstract : Supplemental Digital Content is available in the text